“Influencia del sistema de crianza de cuyes en los costos de producción en CEASA” - Chicaiza Pasato, Andy Fabián (2023)
The research project was madr in the system from Salache Academic Experimental Center (CEASA). In order to determine the guinea pig breeding system in the production costs, to accurately describe the components and value them into an inventory. By making the identification from people, what participated in the project with the aim by choosing the people, who are part this project, the same ones, who are food part, care and design from food components, safety, infrastructure and records the same ones. These components were applied to the charged farmers from feeding the animals, to the Engineer Administrator, interns and students, who are breeding project part in the guinea pig shed. Therefore, it keep month-to month records track from guinea pig breeding system and thus, realizing the fixed and variable costs, feeding costs, population costs, and this, it can be verified, what there are 83 valued males for sale into $830 dollars, with a variable cost $228, a fixed cost $2,250 and with this, having a result a unit production cost 5.50 dollars. And with this, reviewing the money movements into part times from guinea pigs production system with the realization the flow cash indicating the costs of income and expenses.